2003
DOI: 10.1039/b303975g
|View full text |Cite
|
Sign up to set email alerts
|

Ligand design in coordination chemistry: approaches to new catalysts, new materials, and a more sustainable environment

Abstract: An overview of ligand design in the field of coordination chemistry is presented in a perspective format. Four major areas in coordination chemistry, where design and synthesis of ligands are crucial, are reviewed. We show that for successes in research leading towards new catalysts, new materials, insight is biocatalysis and for a sustainable environment, controlled ligand design is a crucial element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 113 publications
0
84
0
Order By: Relevance
“…On the other hand, the reaction of [NbA C H T U N G T R E N N U N G (h 6 -mes) 2 ] with tcne in toluene at room temperature leads instantaneously to a black precipitate, which was analyzed as [NbA C H T U N G T R E N N U N G (tcne) 1 (Table 5). Moreover, preliminary magnetic measurements evidenced that this solvated compound exhibits a spontaneous magnetization at 2 K (H c = 100 Oe).…”
Section: Ligand Exchange In the Preparation Of Solvated [M-mentioning
confidence: 99%
“…On the other hand, the reaction of [NbA C H T U N G T R E N N U N G (h 6 -mes) 2 ] with tcne in toluene at room temperature leads instantaneously to a black precipitate, which was analyzed as [NbA C H T U N G T R E N N U N G (tcne) 1 (Table 5). Moreover, preliminary magnetic measurements evidenced that this solvated compound exhibits a spontaneous magnetization at 2 K (H c = 100 Oe).…”
Section: Ligand Exchange In the Preparation Of Solvated [M-mentioning
confidence: 99%
“…[21] The model complexes 2 a,b [22] were prepared in order to trace the proposed mechanism, but no indication for nucleophilic addition of secondary amines to the coordinated alkene was noted under ambient conditions, see Equation (2).…”
Section: Nucleophilic Addition To Alkenes Coordinated In Transition-mmentioning
confidence: 99%
“…Different approaches are being undertaken to find highly efficient catalysts, in particular for new reaction types and organic transformations, [1] for example, in order to shorten multiple step reaction sequences. A common approach in homogeneous catalysis is the creation of new ligand structures [2] in combination with an appropriate transition-metal center. Furthermore suitable activators, additives, and the reaction medium are also important factors that may affect catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a redox-active blue complex 1 (x = 1.9) and the copper(II) nitrate electron transfer associated with the valence tautomerism are revealed for the first time in copper-based dendrimers. It has been shown that the electronic structure of the blue complex 1 (x = 1.9) is adequately described as a mixed-valence dimer containing d 9 -and diamagnetic d 10 -configurated copper ions, and an antiferromagnetically coupled NO 3 C radical arising on the nitratebridged counter ligand. The activation energy value found for the electron transfer is about 0.35 meV, which indicates a low-energy charge dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The interest in these metallodendrimers is not only based on their applications-they can also be used as models of biological systems. [9] Metal ions play a dominant role in controlling the behaviour of many biologically important macromolecules [10] and metal-ion dendrimers exhibit some bio-related functions, such as electron transfer and the ability to bind oxygen molecules. It is well known that multiple copper ions bound within a spherical dendrimer have been used for O 2 binding, [11] and the copper-ion dendrimer could react with oxygen to form bridged copper complexes.…”
Section: Introductionmentioning
confidence: 99%